Does health literacy affect the decision to have gestational diabetes screening test? - Uyanıklar, Özlem Özgün; Atak, Zeliha; Rahımlı Ocakoglu, Sakine; Ortaç, Hatice; Ocakoğlu, Gökhan (The European Research Journal, 2024)
Objectives: The main objective of this study is to assess the relationship between the level of Health Literacy and the patient's decision to refuse the Gestational diabetes mellitus screening test. Methods: This cross-sectional study was conducted at a high-volume public hospital from March 2020 to September 2020 with women between 24-28 weeks of gestation. Demographic characteristics and gestational diabetes mellitus screening status were recorded for each woman. The European Health Literacy Survey Questionnaire was used to assess health literacy. Results: A total of 364 women were included in the study. Two hundred and three (55.7%) women accepted the gestational diabetes mellitus screening test, and 44.2% did not. Health care, disease prevention, health promotion subscales, and the general scale scores were higher in the gestational diabetes mellitus screening group (p = 0.001, p = 0.024, p = 0.01, and p = 0.003, respectively). It was determined that a 1-point increase in the health care score decreased the probability of rejecting the gestational diabetes mellitus screening by 1.03 times (p = 0.003). Conclusions: Lower health literacy levels were associated with higher rates of gestational diabetes mellitus screening test rejection.